Contextual Teaching and Learning Approach Based On Tpack To Increase Students' Interest In Learning and Learning Outcomes - Wardoyo, Ali; Sunismi, Sunismi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research is a Classroom Action Research (CAR) using Contextual Teaching and Learning (CTL) approach based on TPACK to increase students' interest and learning outcomes. The study involved 22 students of class VII at MTsN 2 Tanah Bumbu, with data collection techniques including observation, written tests, and questionnaires. The results showed that the CTL approach significantly increased students' interest in learning, with their attention to math increasing from 54.55% to 81.82% after the action. In addition, students' feelings of pleasure increased from 36.36% to 77.27%, and their interest in mathematics increased from 31.82% to 63.64%. The CTL approach also improved learning outcomes, with an increase in the average learning outcomes and the level of KKTP (Criteria for Completion of Learning Objectives). The average learning outcome before the action was 46.4, and in cycle I it increased to 59.5 with a completeness percentage of 54.5%. In cycle II, it reached a significant increase of 74.5 with a percentage of 100% completeness.